PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA TOKO A&A COPIER PEMATANGSIANTAR - Togatorop, Joster; Lie, Darwin; Butarbutar, Marisi; Wijaya, Andy (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The results can be summarized as follows: 1. Quality of service, price, customer satisfaction and customer loyalty is good. 2. There is influence of service quality and price to customer satisfaction in prove ŶZ  = 5,885 + 0,523X1 + 0,661X2. The effect of customer satisfaction on customer loyalty is proved Ŷ = 6,197 + 0,663Z. 3. Quality of service and price have high and positive correlation with customer satisfaction in prove with value r = 0,858, and determination value equal to 26,4%. Customer satisfaction has high moderately and positive correlation with customer loyalty in the prove with the value of r = 0.763, and the value of determination of 41,7%. 4. Hypothesis test results stated H0 rejected means the quality of service and price have a positive and significant effect on customer loyalty with customer satisfaction as intervening variable.             The suggestions of this research are: 1. To improve the quality of service, A&A Copier Pematangsiantar shop employees should be able to handle customer complaints optimally, friendly to customers and able to communicate and serve customers well. 2. To optimize prices, to provide discounts to customers who have been copying more than one ream of paper and providing credit cards as a means of payment transactions. 3. For customer satisfaction, improve the results of photocopy so as not to blurred and bilge a more tidy. 4. To improve customer loyalty, pay attention to customer needs, help operate the computer, provide information about the products to be purchased by customers, and give the gift evenly.